MARAQDIA BALANIPA (Studi Pergeseran Peran di Polman Provinsi Sulawesi Barat) - Muhammad Asdar A.B (Jurnal Ilmu Sosiologi Dialektika Kontemporer, 2013)
Commitments in holding and maintaining adat/custom has become one of the factors triggering a shift in the role of the Maraqdia Balanipa in Tinambung District of Polman Regency of West Sulawesi Province. While the modern era is transformed into something that should be acted upon and dealt with, the roles in holding and maintaining custom including maintain the existence of maraqdia in the Mandar region shifted. Regional autonomy in forms of decentralization, also affects the role shift of maraqdia values. As if chasing with time, everybody competes to get positions available. It is undeniable that the maraqdia circles are also taking parts in practical politics which, as a matter of fact, transgressing the norms and values of decency to the commitment of maintaining and preserving the arrajangan Balanipa.Keywords: Maraqdia, Elite, Role Shift